2021
DOI: 10.1016/j.jcvp.2021.100036
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of SARS-CoV-2 and influenza viruses: A systematic review and meta-analysis

Abstract: We conducted this meta-analysis to determine the proportion of co-infection with influenza viruses in SARS-CoV-2 positive patients and to investigate the severity of COVID-19 in these patients. We included studies with SARS-CoV-2 infection confirmed by qRT-PCR and influenza virus infection (A and/or B) by nucleic acid tests. The proportion of co-infection was compared between children and adults, and between critically ill or deceased patients compared to overall patients. Fifty-four articles were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 72 publications
(86 reference statements)
1
42
0
1
Order By: Relevance
“…Several clinical studies have reported coinfection of SARS-CoV-2 with other viruses, including human immunodeficiency virus (HIV), hepatitis B and C viruses (HBV and HCV, respectively), influenza A and B viruses (IAV and IBV, respectively), and dengue virus (DENV) ( 13 19 ). In particular, coinfection with SARS-CoV-2 and IAV was common early in the COVID-19 pandemic, prior to the enforcement of masks and social distancing ( 17 , 20 ). A meta-analysis of published studies from the first 4 months of the pandemic showed viral coinfection with SARS-CoV-2 in 3% of hospitalized COVID-19 patients, with IAV being among the most common coinfecting viruses ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have reported coinfection of SARS-CoV-2 with other viruses, including human immunodeficiency virus (HIV), hepatitis B and C viruses (HBV and HCV, respectively), influenza A and B viruses (IAV and IBV, respectively), and dengue virus (DENV) ( 13 19 ). In particular, coinfection with SARS-CoV-2 and IAV was common early in the COVID-19 pandemic, prior to the enforcement of masks and social distancing ( 17 , 20 ). A meta-analysis of published studies from the first 4 months of the pandemic showed viral coinfection with SARS-CoV-2 in 3% of hospitalized COVID-19 patients, with IAV being among the most common coinfecting viruses ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This happens because the mean incubation and viral shedding times of influenza viruses (2 and 3 days, respectively) are much shorter than those of SARS-CoV-2 (6 and 17 days, respectively). 2 The proportion of coinfection with influenza virus and SARS-CoV-2 among children (3.2%) was remarkably higher than that in adult patients (0.3%), indicating that children are more susceptible to the coinfection. The proportion of coinfection with influenza viruses among critically ill COVID-19 patients (2.2%) was higher than that in overall patients (0.6%), suggesting that coinfection with influenza viruses may aggravate the severity of Indeed, animal studies have shown that simultaneous, or sequential, coinfection by influenza A virus (IAV) and SARS-CoV-2 resulted in more severe weight loss and lung inflammatory damage, as well as increased tissue cytokine/chemokine expression than infection by either IAV or SARS-CoV-2 alone.…”
mentioning
confidence: 88%
“…Results from a meta‐analysis of 54 related publications indicated an overall proportion of coinfection with influenza viruses in SARS‐CoV‐2‐positive patients of 0.7%. 2 An over 18‐month period study with 17,011 adults with SARS‐CoV‐2 infection shows 1.3% of coinfection with influenza viruses. 3 However, the actual coinfection rate may be much higher in that some coinfected patients may have undetectable influenza virus at the time SARS‐CoV‐2 infection is diagnosed.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations